Hierarchical structure of MWCNT reinforced semicrystalline HDPE composites: A contrast matching study by neutron and X-ray scattering. (February 2018) - Liu, Dong; Li, Xueyu; Song, Hongtao; Wang, Pucheng; Chen, Jie; Tian, Qiang; Sun, Liangwei; Chen, Liang; Chen, Bo; Gong, Jian; Sun, Guangai
Graphical abstract: Highlights: Neutron and X-ray scattering are combined as a contrast matching probe. Hierarchical structure of semicrystalline polymer based composite has been studied. A reinforcement model of MWCNTs/HDPE composites are proposed. Abstract: Combining neutron and X-ray scattering (SANS, SAXS, and WAXD) as the contrast matching probes, the hierarchical structures of the multi-wall carbon nanotubes/high density polyethylene (MWCNTs/HDPE) composites (0.1–2.0 wt%) have been studied. SANS measurement avoided the correlation peak associated to the semicrystalline nature of HDPE from SAXS, and the passible scattering from the stretch induced voids. Benefitting from SANS data, the power law ( α ) taking the flexible cylinder suggested that whole MWCNTs in the unstretched composites follow a self-avoiding random walk ( α  ≈ 1.67). SANS data suggest a hollow flexible cylinder structure with outer and inner diameters (core-shell-like cross section) of the scatterers as ca. 12.6 nm and 4.1 nm, while the Kuhn length is about 43.0 nm. Tensile test displayed improved mechanical properties. Interestingly, the Hermans orientation parameter ( f ) of HDPE crystals ( fc ) in the stretched composites are around a plateau ca. 0.96 initially, while decreased remarkably to 0.776 when the fraction is further increased to 2.0 wt%. f obtained by SANS showed a similar tendency (decreased from 0.756 to 0.572). Combining all the results along with differential scanning calorimetry (DSC) measurement, a mechanism of adhered crystals on the surface of MWCNTs and a reinforcement model are proposed.